Apart from Open to all: Assessing the Status and Community participation of the Public Library Nonusers (International Journal of Food and Nutritional Sciences, 2022)
Despite the all-encompassing discourse of open for all and local gateway to information,academic profiling and understanding of the nonusers of public libraries remains weak. In fact,most of the studies concentrate on the library users’ part keeping aside the crucial issue of nonuseof the public libraries. This study attempts to assess and develop an understanding about the publiclibrary nonusers by mapping their socio-demographic characteristics and community participation.